An Analytical Study Of Some Kinematical Variables Affecting The Start Of Backstroke Comparison Between National Iraqi Swimmers and An International Swimmer - Thamir, Ahmed (Journal of Physical Education, 2010)
the Importance of the study lies in the role of kinematical variables in achievements and especially in swimming. Swimming is one of the sports that developed along with the development of technique whether in swimming motion, start or turning. Identifying the technique of the best world swimming champion will help identify the weaknesses and strengths of Iraqi swimmers. The problem of the research lies in the differences in race times especially speed races in Iraqi swimmers compared to the international swimmer. This difference in race times is very huge while it should be splits of the seconds. This encouraged the researcher to study this problem by identifying the weaknesses in Iraqi swimmers' kinematical variables during the performance of backstroke start that plays an important role in shortening the total race time.The procedures of the research:The researcher used the descriptive method. The subjects were (4) Iraqi backstroke league swimmers as well as one international swimmer taken as a model. The Iraqi swimmers were videotaped using camera type Sony with 25 frame /second during the training campus held in turkey in preparations for the eleventh Arabic tournament. A comparison was made between the Iraqi swimmers and the model in some kinematical variables that affect the start of backstroke using dartfish program for analyses. The researcher concluded the following: 1.The international swimmer's achievement in backstroke in the start was better that that of Iraqi swimmers. 2.The best starting achievement in the international swimmer over Iraqi swimmers was due to the speed and angle of release indicate in turn perfect kinematical variables that affect starting backstroke. Finally the he recommended the following; 1.The necessity of training on the start phase of backstroke aiming at the lowest time possible and making sure to push the legs in the perfect manner which allows better horizontal impulse. 2.Artistic performance according to kinematical standards can be easily seen the performance of the international model.